Enoxaparin Prevents Steroid-Related Avascular Necrosis of the Femoral Head - Rainer Beckmann; Hayfaa Shaheen; Nisreen Kweider; Alireza Ghassemi; Athanassios Fragoulis; Benita Hermanns-Sachweh; Thomas Pufe; Mamed Kadyrov; Wolf Drescher (The Scientific World Journal)
Nontraumatic osteonecrosis of the femoral head is still a challenging problem in orthopedic surgery. It is responsible for 10% of the 500,000 hip replacement surgeries in the USA and affects relatively young, active patients in particular. Main reasons for nontraumatic osteonecrosis are glucocorticoid use, alcoholism, thrombophilia, and hypofibrinolysis (Glueck et al., 1997; Orth and Anagnostakos, 2013). One pathomechanism of steroid-induced osteonecrosis is thought to be impaired blood flow to the femoral head caused by increased thrombus formation and vasoconstriction. To investigate the preventive effect of enoxaparin on steroid-related osteonecrosis, we used male New Zealand white rabbits. Osteonecrosis was induced by methylprednisolone-injection (1×20 mg/kg body weight). Control animals were treated with phosphate-buffered saline. Treatment consisted of an injection of 11.7 mg/kg body weight of enoxaparin per day (Clexane) in addition to methylprednisolone. Four weeks after methylprednisolone-injection the animals were sacrificed. Histology (hematoxylin-eosin and Ladewig staining) was performed, and empty lacunae and histological signs of osteonecrosis were quantified. Histomorphometry revealed a significant increase in empty lacunae and necrotic changed osteocytes in glucocorticoid-treated animals as compared with the glucocorticoid- and Clexane-treated animals and with the control group. No significant difference was detected between the glucocorticoid and Clexane group and the control group. This finding suggests that cotreatment with enoxaparin has the potential to prevent steroid-associated osteonecrosis.